Rancang Bangun Sistem Informasi Perencanaan Bahan Baku Produksi Batu Pada PT. Kartika Jaya Abadi Beton - Cendrakasih, Titis; Tanuwijaya, Haryanto; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
PT. Kartika Abadi Jaya Beton is a company that started its production activities of crushing rock metamorphic types and sell them in large and small parties. Currently the company purchased raw materials based on company policy that in one day the rock breaking machine have to process at least 18 tonnes of raw material without any calculation. As a result, the products produced by the raw materials are not able to fulfill customer orders.From the problems it created an information system planning of raw material for production of stone is capable of calculating the amount of raw materials needed every day.Calculation of raw materials using a percentage of stone-crushing machines that it adjusted of customer orders.By using the information system planning raw material for the production of rock that’s capable to calculate raw material each day. The company can use it to buy raw materials in accordance with the needs of the existing order. Information systems planning raw material for the production of stone is also able to display a graphical report on the status of orders, inventory status, receipt of raw materials, production and graphic recap sales reports based on the number of product sales.